2018
DOI: 10.1111/cas.13597
|View full text |Cite
|
Sign up to set email alerts
|

Early disease progression in patients with localized natural killer/T‐cell lymphoma treated with concurrent chemoradiotherapy

Abstract: Prognosis of patients with localized nasal extranodal natural killer/T‐cell lymphoma, nasal type (ENKL) has been improved by non‐anthracycline‐containing treatments such as concurrent chemoradiotherapy (CCRT). However, some patients experience early disease progression. To clarify the clinical features and outcomes of these patients, data from 165 patients with localized nasal ENKL who were diagnosed between 2000 and 2013 at 31 institutes in Japan and who received radiotherapy with dexamethasone, etoposide, if… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 24 publications
(60 reference statements)
4
12
0
Order By: Relevance
“…Regarding ENKTCL patients who failed to achieve PFS24, the median OS after progression was only 5.3 months, indicating that few patients who suffer early progression can be successfully treated. As observed by other studies [35,36], ENKTCL patients who suffer disease progression after initial treatment had extremely poor prognoses, regardless of stage or risk group. In a recent study of 179 patients with ENKTCL who suffered disease relapse or progression after initial non-ANT-based chemotherapy, the median OS was only 6.4 months [35].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Regarding ENKTCL patients who failed to achieve PFS24, the median OS after progression was only 5.3 months, indicating that few patients who suffer early progression can be successfully treated. As observed by other studies [35,36], ENKTCL patients who suffer disease progression after initial treatment had extremely poor prognoses, regardless of stage or risk group. In a recent study of 179 patients with ENKTCL who suffered disease relapse or progression after initial non-ANT-based chemotherapy, the median OS was only 6.4 months [35].…”
Section: Discussionsupporting
confidence: 66%
“…As observed by other studies [35,36], ENKTCL patients who suffer disease progression after initial treatment had extremely poor prognoses, regardless of stage or risk group. In a recent study of 179 patients with ENKTCL who suffered disease relapse or progression after initial non-ANT-based chemotherapy, the median OS was only 6.4 months [35]. Similarly, for patients who failed to achieve PFS24 or EFS24, the subsequent median OS was 7.2 months after ANT-based immunochemotherapy for DLBCL and 4.9 months after ANT-based chemotherapy for PTCL [28,29].…”
Section: Discussionsupporting
confidence: 66%
“…The Ki-67 index ranged 30%–80% [ 3 ]. Authors suggested that the outcome of laryngeal T lymphoma was bleak, more than half of them (73.1%) died with earlier treatment either from tumor dissemination or severe laryngeal complications, such as bleeding or obstruction [ 5 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies comparing the outcomes of concurrent, sequential, and sandwich chemoradiotherapy have shown similar efficacy, although these were based on the results of retrospective and indirect comparisons [45, 46]. The long-term outcomes of patients receiving concurrent chemoradiotherapy regimens including DeVIC and VIDL in Japan and Korea were also similar [47]. Therefore, all these approaches may be recommended as a first-line treatment for localized nasal ENKTL.…”
Section: Introductionmentioning
confidence: 99%
“…For example, if patients relapse locally confined to nasal cavity without systemic symptoms and the time to relapse is longer than at least 2 years, retreatment with concurrent or sequential or sandwich chemoradiotherapy may be tried, as for newly diagnosed patients. However, if disease relapse occurs within 2 years after the completion of first-line treatment, systemic chemotherapy should be considered because the outcome of early disease relapse was found to be poor in a recent retrospective study of patients with localized nasal ENKTL receiving concurrent chemoradiotherapy [47].…”
Section: Introductionmentioning
confidence: 99%